Catalytic Activity of Zr4+/ZA on The Isomerization Reaction of α-Pinene and It’s Reusability Test - Nico Aditya Wijaya; Nanik Wijayati; Edy Cahyono (Indonesian Journal of Physics and Nuclear Applications, 2016)
Production of turpentine oil from pine resin until December 2014th was reported to reaching 17.150 tones with the wide of pine forest is 876.992,66 acres. The main component of turpentine oil is α-pinena which isomer products have high value for industrial raw materials. Effects concentration of impregnation and reusability test a best catalyst on α-pinene isomerization reaction using catalysts Zr4+/natural zeolite in which modificated with different Zr4+ concentration were analyzed. Characterization of catalyst included X-ray Fluoroscent for detection of Zr concentration in natural zeolites, Surface Area Analyzer  for determine catalyst porosity using BET method, and determination of acidity using vapor ammonia and pyridine base adsorption gravimetric method. Isomerization process used a batch reactor with variation in the concentrations of Zr4+ impregnations 10, 15, and 20 w/w as well as reusability test used best catalyst. The highest conversion of α-pinene  used Zr4+/ZA 10% catalyst was 3,89% so as Zr4+/ZA 10% catalyst is best catalyst than other catalysts whereas highest conversion of α-pinene used Zr4+/ZA 10% regeneration catalyst was 4,26%. The product is produced from isomerization reaction of α-pinene used Zr4+/ZA all variations catalysts was camphene and limonene.